Nkunimdie Christology: An Akan contextual expression of the Christus Victor motif of atonement - I. Boaheng (Acta Theologica)
The Akan community of Ghana has a large Christian following. Nonetheless, many Akan believers still consult traditional priests for protection, wealth, and power. This happens not because these Christians doubt the theological fact that Christ offered an atonement, but because they do not consider the atonement as providing them with adequate protection against evil forces. This situation makes the quest to closely investigate their concept of Christ fairly urgent and useful. To address the issue, there is the need to project Christ’s power over evil forces. One of the models of atonement that is helpful in this regard is the Christus Victor which emphasises the victory that Christ won over Satan and his host through his death on the cross. This research, therefore, aims to give contextually express the Christus Victor motif of Christ’s atonement from an Akan Christian perspective. This research is based on literature involving theological and ethical analyses of, and reflections on the Christus Victor model of atonement and how it can address the Akan Christian need for spiritual protection and economic liberation. The resulting theology is a contextual theology that incorporates the biblical world view, the Akan world view, and the Christus Victor model of atonement. Thus, the article seeks to bring about positive reforms in Akan religio-ethical beliefs and practices, and hence empower Akan Christians not only to discontinue their reliance on traditional powers, but also to have complete trust in Christ’s atonement alone as means of providing them with all their physical and spiritual needs.